2013
DOI: 10.1073/pnas.1303510110
|View full text |Cite
|
Sign up to set email alerts
|

Unique drug screening approach for prion diseases identifies tacrolimus and astemizole as antiprion agents

Abstract: Prion diseases such as Creutzfeldt-Jakob disease (CJD) are incurable and rapidly fatal neurodegenerative diseases. Because prion protein (PrP) is necessary for prion replication but dispensable for the host, we developed the PrP-FRET-enabled high throughput assay (PrP-FEHTA) to screen for compounds that decrease PrP expression. We screened a collection of drugs approved for human use and identified astemizole and tacrolimus, which reduced cell-surface PrP and inhibited prion replication in neuroblastoma cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 54 publications
(48 reference statements)
2
76
2
Order By: Relevance
“…Karapetyan and colleagues reported two PrPc-reducing compounds: astemizole, which stimulates autophagy but does not modify PrPc levels at a dose preventing prion replication; and tacrolimus, which reduces both membrane and intracellular PrPc levels by a nontranscriptional mechanism (33). Tacrolimus has also been reported by other researchers to suppress the neurodegenerative process of prion-infected animals as a calcineurin inhibitor (34) and to activate autophagy in both prion-infected neuroblastoma cells and animals (35).…”
Section: Discussionmentioning
confidence: 93%
“…Karapetyan and colleagues reported two PrPc-reducing compounds: astemizole, which stimulates autophagy but does not modify PrPc levels at a dose preventing prion replication; and tacrolimus, which reduces both membrane and intracellular PrPc levels by a nontranscriptional mechanism (33). Tacrolimus has also been reported by other researchers to suppress the neurodegenerative process of prion-infected animals as a calcineurin inhibitor (34) and to activate autophagy in both prion-infected neuroblastoma cells and animals (35).…”
Section: Discussionmentioning
confidence: 93%
“…The diffusion coefficients at pH 4.4 in the presence of 0-1.5 M GdnHCl are similar to that of the reduced protein at the same denaturant concentration, but the average Trp-Cys distance at pH 4.4 increases as denaturant is reduced. We used the condition at pH 4.4, 0 M GdnHCl to investigate the effect of astemizole, an antihistamine drug, recently found to exhibit anti-prion activity and prolong the survival of prion-infected mice (51). The physical basis of the mechanism of this drug is unknown as is the binding site.…”
Section: Resultsmentioning
confidence: 99%
“…At pH 4.4, such as found in the endosome, the hamster diffuses in the intermediate regime that has been observed for other aggregation-prone sequences, but rabbit diffuses in the fast regime observed for non-aggregation-prone disordered sequences. Furthermore, the addition of astemizole, an antihistamine drug which was previously reported as an anti-prion candidate (51), to the hamster sequence appears to speed up diffusion of the protein chain out of aggregation prone regime. Therefore, the prion protein is observed to occupy all diffusive regimes under different conditions and with sequences from different species.…”
mentioning
confidence: 99%
“…Moreover, conditional knockout of Prnp expression halted disease progression and recovered certain brain functions even after disease onset (Mallucci et al 2002(Mallucci et al , 2003 (Karapetyan et al 2013). For example, the compound tacrolimus has been shown to reduce both membrane and intracellular PrP C levels by a nontranscriptional mechanism (Karapetyan et al 2013), to suppress neurodegenerative processes in prioninfected animals by acting as a calcineurin inhibitor (Mukherjee et al 2010), and to activate autophagy in both prion-infected cells and animals (Nakagaki et al 2013).…”
Section: Insights From Therapeutic Studies For Prp Prion Diseasementioning
confidence: 99%
“…Accordingly, Venko et al (2014) computationally analyzed and summarized structure-activity relationships of small organic compounds using prion-infected cell-based assays. Kamatari et al (2013) (Heiseke et al 2010), and autophagy-related antiprion compounds, including astemizole (Karapetyan et al 2013) and tacrolimus (Nakagaki et al 2013), are reported to have certain effects in prion-infected animals. Conversely, Marzo et al (2013) have recently reported that 4-hydroxytamoxifen conveys PrP C and PrP Sc to lysosomes independent of autophagy, suggesting the existence of a lysosomal degradation pathway for PrP Sc clearance.…”
Section: Insights From Therapeutic Studies For Prp Prion Diseasementioning
confidence: 99%